INNOVATIVE METHODS OF OIL EXTRACTION FROM DEEP DEPOSITS - Boyqobilova Makhliyo Makhmudovna; Rakhimboyev Norbek Ilkhom ugli; Mukhtorov Abdulrakhmon Dilshodbek ugli (American Journals Publishing, 2024)
Obviously, this method is characterized by a high degree of theoretical justification of the oil recovery mechanism and eliminates error due to the human factor due to the use of software and computing systems. This path, on the one hand, is very labor-intensive, and on the other hand, there is not always reliable information about the properties of productive formations.
Keywords: Carbonate reservoirs, geologic model, waterflooding. Oil, product, high oil viscosity